In and out of unemployment: Labour market transitions and the role of testosterone - Peter Eibich; Ricky Kanabar; Alexander Plum; Julian Schmied (University of Essex, Institute for Social and Economic Research (ISER), 2021)
Biological processes have provided new insights into diverging labour market trajectories. This paper uses population variation in testosterone levels to explain transition probabilities into and out of unemployment. We examine labour market transitions for 2,004 initially employed and 111 initially unemployed British men from the UK Household Longitudinal Study ("Understanding Society") between 2009 and 2015. We address the endogeneity of testosterone levels by using genetic variation as instrumental variables (Mendelian Randomization). We find that for both initially unemployed men as well as initially employed men, higher testosterone levels reduce the risk of unemployment. Based on previous studies and descriptive evidence, we argue that these effects are likely driven by differences in cognitive and non-cognitive skills as well as job search behaviour of men with higher testosterone levels. Our findings suggest that latent biological processes can affect job search behaviour and labour market outcomes without necessarily relating to illness and disability.
Keywords: I10; J64; C23; 330; labour market dynamics; unemployment; testosterone